Influence of [Mo6Br8F6]2− Cluster Unit Inclusion within the Mesoporous Solid MIL-101 on Hydrogen Storage Performance - Dybtsev, Danil; Serre, Christian; Schmitz, Barbara; Panella, Barbara; Hirscher, Michael; Latroche, Michel; Llewellyn, Philip L; Cordier, Stéphane; Molard, Yann; Haouas, Mohamed; Taulelle, Francis; Férey, Gérard (Langmuir, 2010)
The inclusion of (TBA)2Mo6Br8F6 (TBA = tetrabutylammonium) containing [Mo6Br8F6]2− cluster units within the pores of the mesoporous chromium carboxylate MIL-101 (MIL stand for Materials from Institut Lavoisier) has been studied. X-ray powder diffraction, thermal analysis, elemental analysis, solid-state NMR, and infrared spectroscopy have evidenced the successful loading of the cluster. In a second step, the hydrogen sorption properties of the model cluster loaded metal organic framework (MOF) system have been analyzed and compared to those of the pure MOF sample, through a combination of adsorption isotherms (77 K, room temperature), thermal desorption spectroscopy, and calorimetry (calculated and experimental) in order to evaluate the hydrogen storage efficiency of the cluster loading.